Come and play: interactive theatre for early years - Patel, Roma; Schnadelbach, Holger; Koleva, Boriana (2017)
The convergence of theatre and digital technologies can play a valuable role in theatre for early years, but, how an audience of under-5’s experiences and engages with these spaces is largely unexplored. We present an interactive performance installation and demonstrate how concepts from early years practice, in particular schemas, children’s repeated play patterns, can be used as a design framework. We integrated sensors and microcontrollers into objects, puppets, and scenography and invited eight groups of very young children and their grownups to explore the performance. We discuss how schemas are useful as a design and analysis tool in TEY, how schemas need to be expanded to include multi-sensory interactions with hybrid physical-digital objects, and how designers need to consider the roles of adults who scaffold interaction between very young children and their surroundings.